Sunnah Siwakan in Health Science Perspektif and Power of Faith - A'yun, Qurrotul (Journal Intellectual Sufism Research (JISR), 2019)
Siwakan is the prophet's sunnah which aims to cleanse the mouth and teeth using araak wood (Salvadora persica). Woodwood contains various chemicals that can prevent plaque from appearing and have the potential to be antibacterial. Siwak can also be used to strengthen memorization because it can make a loss of laziness. The purpose of this study was to determine the benefits of sunny siwakan in health sciences and memorizing power. In this study used a library research where data will be obtained from books, journals, magazines, documents, records of historical stories, or pure library research related to the object of research. The results showed that Bachtiar from the Faculty of Medicine University of Indonesia said araak wood contained trimethylamine (TMA) which was able to prevent plaque from forming a nest of germs so that teeth became healthy and other results from the Ta'lim Muta'allim book showed that civet could eliminate phlegm where phlegm is one of the causes of lazy memorization.